(untitled) (Comparative & International Education Series, 2022)
This chapter is a personal narrative and reflection on personal experiences as an international doctoral student which highlights the author’s challenges in her journey. Reflecting on previous experiences teaching in international schools around the world, and her identity as an expatriate teacher, the author shares some of her experiences as an international doctoral student while highlighting the identity challenges she encountered at the beginning of her PhD program. Through personal stories, the author presents her experiences with feelings of belonging and the process of identity shift. This chapter provides insights into her identity journey and diversity as she experienced it.